“If I am from Megara.” Introduction to the Local Discourse Environment of an Ancient Greek City-State - Beck, Hans (Teiresias Supplements Online, 2018)
The introduction to the volume discusses, first, the conceptual framework of localism and the local in the ancient Greek world. Each city-state cultivated its own identity of place. In doing so, the polis was subject to a local discourse environment that set it apart from other cities. In the second section, the article examines the various manifestations of this environment in Megara, exploring multiple facets and fragments of the local discourse in the city. In sum, the author looks at Greek history through a decidedly local lens, explaining how the Megarians viewed the world around them and what it meant ‘to be from Megara’.